2017
DOI: 10.1007/s00737-017-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of participating in a prospective, longitudinal postpartum depression study: insights for perinatal mental health researchers

Abstract: Barriers to recruitment for research on mental illness include participant distrust of researchers and social stigma. Though these issues may be acutely important in perinatal mental health research, they remain unexplored in this context. In order to inform strategies to more fully engage women in perinatal mental health research, we explored the motivations and experiences of women with a history of major depressive disorder who participated in a prospective longitudinal research study on postpartum depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…Overall, the percentage of participants who received treatment was small, at less than 10% of the total sample. But even amongst women who were not treated, the repeated SCID interviews in and of themselves may have had a therapeutic effect by providing women with an opportunity to talk about symptoms in an open manner to a healthcare professionalan opportunity which in this setting is rare [24]. Depression of any severity was more likely to persist over the course of the perinatal period than depression of moderate-severe severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the percentage of participants who received treatment was small, at less than 10% of the total sample. But even amongst women who were not treated, the repeated SCID interviews in and of themselves may have had a therapeutic effect by providing women with an opportunity to talk about symptoms in an open manner to a healthcare professionalan opportunity which in this setting is rare [24]. Depression of any severity was more likely to persist over the course of the perinatal period than depression of moderate-severe severity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence consistently suggests that prevalence is higher in low-and middle-income countries (LMIC), with estimates ranging from 10. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].3% in LMIC compared with 7.4-19.2% in high-income countries (HIC) [1,3,4]. Untreated perinatal depression has been associated with a number of significant adverse outcomes including negative health behaviours in pregnancy [1], subsequent chronic and recurrent depression [1,2], impaired ability to work and provide care, relationship breakdown [2,5] and suicidean important contributor to maternal deaths globally [6,7].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women report that they do not participate in research studies because they often lack interest in or distrust scienti c research [6,9,10], experience disapproval from friends and family [3,5], and feel as though they do not have time to participate [5,9]. On the other hand, pregnant women indicate they are motivated to participate when they receive personal bene ts, including the potential for improved pregnancy outcome [48,49], health education [50], and improvements to their own health [10,48]. Altruistic reasons, such as helping future patients [49] and contributing to knowledge, also spur participation in research studies [9,10,48,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pregnant women indicate they are motivated to participate when they receive personal bene ts, including the potential for improved pregnancy outcome [48,49], health education [50], and improvements to their own health [10,48]. Altruistic reasons, such as helping future patients [49] and contributing to knowledge, also spur participation in research studies [9,10,48,[50][51][52]. For example, Daniels et al [51] found that 93% of pregnant women were motivated to participate in a study because they would contribute to science.…”
Section: Discussionmentioning
confidence: 99%